The development of stone sculpting craftsmen in Jatisumber Village, Trowulan District, Mojokerto Regency - Rachmad Ilham; Mukhlis, Imam (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this study is to comprehensively analyze the challenges faced by craftspeople, assess their level of expertise, explore the obstacles they experience in terms of business competitiveness, and provide strategies or models to empower them.     The study utilizes the community empowerment paradigm, which focuses on collective endeavors to improve social well-being and strengthen relationships among community groups. Empowerment requires actively involving external entities to achieve goals and making efforts to acquire resources. This study utilizes a qualitative research methodology. Primary data sources consist of unprocessed data acquired directly from interviews and observations. A total of seven individuals were interviewed using a semi-structured interview format. In addition, this study utilized supplementary data sources such as statistical data, theses, and government papers. The findings indicate that the empowerment of stone statue makers in Jatisumber Village involves various aspects.     The primary areas that necessitate heightened attention in empowerment projects are marketing, promotion, financing, networking, and regeneration. The fundamental obstacles encountered by artisans are directly associated with these elements.     Empowerment requires the cooperation of several parties, such as the government, private sector, community, and artisans themselves. The primary objective of this study is to thoroughly identify the difficulties faced by stone statue craftsmen, evaluate their workforce skills, analyze the barriers they encounter in their economic pursuits, and suggest strategies for empowerment that involve multiple stakeholders, all with the aim of improving the livelihoods of these craftsmen.